2011
DOI: 10.1186/1743-422x-8-391
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing activities of caprine antibodies towards conserved regions of the HCV envelope glycoprotein E2

Abstract: Anti HCV vaccine is not currently available and the present antiviral therapies fail to cure approximately half of the treated HCV patients. This study was designed to assess the immunogenic properties of genetically conserved peptides derived from the C-terminal region of HVR-1 and test their neutralizing activities in a step towards developing therapeutic and/or prophylactic immunogens against HCV infection. Antibodies were generated by vaccination of goats with synthetic peptides derived from HCV E2. Viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Huh7.5 cells were cultured according to previously described protocol where Huh7.5 cells were cultured till adherent cells became semi-confluent, cells were subcultured and counted. [17] Then cells were infected with positive HCV serum according to protocols described by Seipp et al [28] The total cellular RNA was extracted using acid guanidinium-phenol-chloroform according to the protocol of Chomczynski and Sacchi [29] and Goergen et al [30] The successful viral infection in Huh7.5 cells throughout the culture duration was confirmed at the transcriptional level qualitatively by Reverse Transcription Polymerase Chain Reaction (RT-PCR) amplification of HCV RNA and quatitatively by real-time RT-PCR. [17,31] Moreover, the HCV viral proteins in transfected cells were detected using immunostaining assay as previously described to confirm that direct infection of Huh7.5 cells resulted in viral replication and de novo synthesis of non structural proteins.…”
Section: Synthesis Of the Virocidal Peptidementioning
confidence: 97%
See 2 more Smart Citations
“…Huh7.5 cells were cultured according to previously described protocol where Huh7.5 cells were cultured till adherent cells became semi-confluent, cells were subcultured and counted. [17] Then cells were infected with positive HCV serum according to protocols described by Seipp et al [28] The total cellular RNA was extracted using acid guanidinium-phenol-chloroform according to the protocol of Chomczynski and Sacchi [29] and Goergen et al [30] The successful viral infection in Huh7.5 cells throughout the culture duration was confirmed at the transcriptional level qualitatively by Reverse Transcription Polymerase Chain Reaction (RT-PCR) amplification of HCV RNA and quatitatively by real-time RT-PCR. [17,31] Moreover, the HCV viral proteins in transfected cells were detected using immunostaining assay as previously described to confirm that direct infection of Huh7.5 cells resulted in viral replication and de novo synthesis of non structural proteins.…”
Section: Synthesis Of the Virocidal Peptidementioning
confidence: 97%
“…[17,31] Moreover, the HCV viral proteins in transfected cells were detected using immunostaining assay as previously described to confirm that direct infection of Huh7.5 cells resulted in viral replication and de novo synthesis of non structural proteins. [17,32] Transfection of Huh7.5 Cell Line with HCV cc J6/JFH…”
Section: Synthesis Of the Virocidal Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies focused on certain peptide sequences from envelope regions 1 and 2 of HCV as a candidate vaccine. They found that peptide region E1 (aa 315-323) and peptide regions from HCV E2 (aa 412-219) and HCV E2 (aa 517-531) had capability to introduce neutralizing antibodies in mice, rabbits, and goats, while peptide sequence from HCV E2 (aa 430-447) produced nonneutralizing antibodies, which are known interference antibodies [15][16][17][18][19][20][21][22]. Another strategy is to use viral vectors inducing T-cell responses against HCV-infected cells, e.g., adenoviral vectors that have big areas of the HCV genome itself.…”
Section: Hcv Vaccine Strategiesmentioning
confidence: 99%
“…Several highly conserved sites were determined in HCV envelope proteins E1 and E2 (Sobolev et al, 2000); however, most these sites did not elicit specific antibodies because of insufficient Tlymphocyte help resulting from the absence of T-helper epitopes in the vicinity. Conjugation of putative B-epitopes, derived from HCV envelope proteins, to promiscuous T-helper epitopes from other sources (Torresi et al, 2007) or to the carrier protein, keyhole limpet hemocyanin (El Awady et al, 2010;El Abd et al, 2011), resulted in the formation of immunogens capable of producing antibodies specific for the whole HCV envelope proteins and viral particles. However, the use of foreign T-epitopes and carrier proteins leads to the formation of T helper memory cells that are non-specific for HCV and hence, will not be activated upon HCV infection.…”
Section: Peptide Immunogens For Anti-hcv Vaccines Under Developmentmentioning
confidence: 99%